2019
DOI: 10.19080/ijcsmb.2019.06.555676
|View full text |Cite
|
Sign up to set email alerts
|

Markers for the Characterization of Liver Mesenchymal Stem Cell

Abstract: LMSCs and BMSCs from other speciesIn mice, LMSCs and BMSCs have nearly identical markers since both cell types are positive for CD44, CD29 CD105, CD49e, CD90 and Sca-1. However, mouse LMSCs are positive for CD73 [21], and mouse BMSCs have low expression of CD73 [22]. In rats, there are no studies on LMSCs; however, Payushina et al.[23] indicated that LMSCs are positive for expression of CD90.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…But there were some findings mentioned by (13) in rabbits cleared CD105 was absent from rabbit MSCs, besides ( 9) and (10) in humans. The positive expression of CD106 was similar to previous reports in humans (4). While (13) in rabbits disagreed with CD106 positive expression, they confirmed that CD106 was absent from the rabbit and human MSCs.…”
Section: Flow Cytometrysupporting
confidence: 87%
See 2 more Smart Citations
“…But there were some findings mentioned by (13) in rabbits cleared CD105 was absent from rabbit MSCs, besides ( 9) and (10) in humans. The positive expression of CD106 was similar to previous reports in humans (4). While (13) in rabbits disagreed with CD106 positive expression, they confirmed that CD106 was absent from the rabbit and human MSCs.…”
Section: Flow Cytometrysupporting
confidence: 87%
“…MSCs/stromal stem cells were first isolated from the bone marrow (4). Although the bone marrow was considered the common source for MSCs, they could be isolated from other sources, taking into consideration the differences in surface markers, proliferation rates, and differentiation ability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These cells express mesenchymal markers such as CD29, CD44, CD73, CD90, HLA-Class I, etc. [32]. Still, the expression levels of these markers vary in reports from different authors.…”
Section: Morphology and Phenotype Of Human Liver Mscsmentioning
confidence: 99%